2016
DOI: 10.1002/pd.4773
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free DNA testing in the maternal blood in high-risk pregnancies after first-trimester combined screening

Abstract: Objective The objective of this study was to investigate a strategy for clinical implementation of cell-free DNA (cfDNA) testing in high-risk pregnancies after first-trimester combined screening.Methods In 259 singleton pregnancies undergoing invasive testing after first-trimester combined screening, a maternal blood sample was sent to the laboratory Natera for cfDNA testing using a single-nucleotide polymorphismbased methodology.Results The cfDNA test provided a result in 249 (96.1%) pregnancies and, among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
2
13
0
1
Order By: Relevance
“…Alternatively to universal screening by cfDNA, some authors have suggested a strategy of cfDNA contingent to first‐line screening by CT as more cost effective . In this case, women with high risk at the CT are referred for invasive testing and women with intermediate risk (cut‐off depending on financial means) are offered cfDNA . This results in higher sensitivity and specificity at considerably lower costs.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively to universal screening by cfDNA, some authors have suggested a strategy of cfDNA contingent to first‐line screening by CT as more cost effective . In this case, women with high risk at the CT are referred for invasive testing and women with intermediate risk (cut‐off depending on financial means) are offered cfDNA . This results in higher sensitivity and specificity at considerably lower costs.…”
Section: Discussionmentioning
confidence: 99%
“…In two of the 35 studies, some of the maternal blood samples for the cfDNA analysis were obtained after the invasive test 16,19 . In 18 studies, it was stated explicitly [7][8][9][10][11][12][13][14][15]18,[20][21][22]27,32,35,37,40 , and in 10 it was assumed on the basis of the described methodology 17,26,[28][29][30][31]33,34,36,38 , that, if an invasive test was carried out, the samples for cfDNA analysis were obtained before the invasive test. In five studies it was uncertain if invasive testing was before or after maternal blood sampling for the cfDNA test 6,[23][24][25]39 .…”
Section: Data Sourcesmentioning
confidence: 99%
“…*Bivariate random-effects regression model. 7 8 8 (100.0, 63.1-100.0) 100 0 (0.00, 0.00-3.62) Liang (2013) 11 5 5 (100.0, 47.8-100.0) 401 1 (0.25, 0.01-1.38) Nicolaides (2013) 12 2 2 (100.0, 15.8-100.0) 227 0 (0.00, 0.00-1.61) Song (2013) 13 3 2 (66.7, 9.4-99.2) 1737 † 0 (0.00, 0.00-0.21) Comas (2014) 17 0 -315 1 (0.32, 0.01-1.76) Porreco (2014) 20 9 9 (100.0, 66.4-100.0) 3269 11 (0.34, 0.17-0.60) Shaw (2014) 21 3 3 (100.0, 29.2-100.0) 192 0 (0.00, 0.00-1.90) Song (2015) 27 0 -203 1 (0.49, 0.01-2.71) Persico (2016) 35 3 2 (66. 7, 9.4- Jiang (2012) 6 3 3 (100.0, 29.2-100.0) 900 0 (0.00, 0.00-0.41) Lau (2012) 7 1 1 (100.0, 2.5-100.0) 107 0 (0.00, 0.00-3.36) Liang (2013) 11 3 3 (100.0, 29.2-100.0) 403 1 (0.25, 0.01-1.37) Porreco (2014) 20 6 6 (100.0, 54.1-100.0) 3263 5 (0.15, 0.05-0.36) Shaw (2014) 21 1 1 (100.0, 2.5-100.0) 194 0 (0.00, 0.00-1.88) Song (2015) 27 1 0 (0.0, 0.0-97.5) 202 0 (0.00, 0.00-1.81) Persico (2016) 35 1 1 (100.0, 2.5-100.0) 248 0 (0.00, 0.00-1.48) Zhang (2016) 39 1 1 (100.0, 2.5-100.0) 86 0 (0.00, 0.00-4.20) Pooled analysis (% (95% CI))* 100 (83.6-100) 0.004 (0-0.08) I 2 (%) 0 0…”
Section: Monosomy Xmentioning
confidence: 99%
“…In this strategy, it was considered to offer an invasive procedure to patients with no results at cfDNA testing only if the CT was positive (risk ≥1: 250) for at least one twin. The implementation of cfDNA testing contingent to the results of combined screening has been shown to be effective in reducing the invasive testing rate in singleton pregnancies [11,12,20]. In addition, a recent study showed that the results of combined screening are useful in the clinical management of cases with a cfDNA test failure [21].…”
Section: Discussionmentioning
confidence: 99%